PENILAIAN KINERJA RUMAH SAKIT DAERAH KOTA BLITAR: PRESPEKTIF VALUE FOR MONEY - Prastiwi, Elisa Eka; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out how the measurement concept of value for money is implemented in assessing the performance of Rumah Sakit Umum Daerah Mardi Waluyoof Blitar city.This research conducted by using qualitative approach. The data collection technique is carried out by using documentary and interview technique whereas the data analysis technique is carried out by using descriptive qualitative.The result of research shows the hospital has successfully achieved the expected efficiency and effectiveness level. The efficiency performance considered from comparison between input and output in which work program plan and activity of agency can be achieved and realized in accordance with expected target. Meanwhile, the effectiveness performance can be seen from the results of achievement input and output in objectives can be realized in accordance with the expected target. Even though the efficiency and the effectiveness of performance the hospital can be achieved, nevertheless the development to performance indicator value for money is needed. So, it can explain comprehensively performance achievement the hospital either it is seen from management capability in obtaining and using their economic resources or the capability in achieving operational objectives.Keywords: Performance, Hospital, Value for Money